Atlantic-wide connectivity of Ascension Island green turtles revealed by finer-scale mitochondrial DNA markers - Sophia A. Coveney; Eva Jiménez-Guri; Samantha Ball; Nathalie Mianseko; Annette C. Broderick; Brendan J. Godley; Joana M. Hancock; Welton Quirino Pereira; Aissa Regalla; Rita Gomes Rocha; Cheibani Senhoury; Benoit de Thoisy; et al. (Conservation Genetics, 2025)
Marine turtles undertake long migrations across different geographies and habitats, exposing them to a wide range of threats throughout their lifespan. Analysing population structure and connectivity is key to informing effective conservation management. We expand knowledge of Atlantic-wide connectivity of green turtles ( Chelonia mydas ) by characterising the genetic structure of the Ascension Island nesting population, one of the largest in the Atlantic Ocean, and carrying out Atlantic population structure and mixed stock analyses using high-resolution genetic markers. We amplified a ~ 738 bp fragment (extended D-loop) and a highly polymorphic mitochondrial short tandem repeat (mtSTR) fragment of the mitochondrial DNA control region, designating haplotypes based on (1) extended D-loop and (2) the extended D-loop and mtSTR combined. Overall, 11 extended D-loop and 33 combined haplotypes were found, the dominant haplotypes being CM-A8.1 and CM-A8.1/7-12-4-4. Population structure analysis found three main genetic groups: Northwest Atlantic, Northern South America, and South and East Atlantic. Mixed stock analyses indicate Ascension Island as a major source for juvenile foraging aggregations in the Southwest Atlantic (34–55%) and Central Africa (18–78%), with some contribution to West Africa (3–20%). Green turtles are vulnerable to fishery bycatch in the coastal waters of the South and East Atlantic. Our study underlines how improving sample sizes of Atlantic mtSTR haplotypes could further elucidate green turtle connectivity across threatened regions. We urge international collaboration to minimise mtSTR data gaps, in order to enhance connectivity assessments and improve conservation measures between countries that share populations.

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Developing Capacity for Transdisciplinary Studies of Changing Ocean Systems - Paul Renaud; Andrea Belgrano; Sam Dupont; Philip Boyd; Sinead Collins; Thomas Blenckner; Michael Drexler; Jason Hall-Spenser; Carol Robinson; Charlotte Weber; Cristian Vargas (Oceanography, 2025)
Addressing global challenges such as climate change requires large-scale collective actions, but such actions are hindered by the complexity and scale of the problem and the uncertainty in the long-term benefit of short-term actions (Jagers et al., 2019). In addition to climate change, socio-ecological systems face the cumulative pressures associated with resource needs, technology development, industrial expansion, and area conflicts. In marine systems, this has been called “the blue acceleration” (Jouffray et al., 2020) and is referred to as “socio-ecological pressures” in this paper. These socio-ecological pressures reduce our ability to reach the UN Sustainable Development Goals and meet the challenges of the UN Ocean Decade, and require integrating knowledge within a shared conceptual framework. For example, achieving sustainable growth must integrate ecological, socioeconomic, and governance perspectives on a larger scale by considering ecological impacts, ecosystem carrying capacities, economic trade-offs, social acceptability, and policy realities. This requires capacity development whereby actors unite to bridge disciplinary boundaries to meet challenges of complex systems.

Evaluation of two fish-based indices of biotic integrity for assessing coldwater stream health and habitat condition in Iowa’s driftless area, USA - Sam Grinstead; Brett Kelly; Michael Siepker; Michael J. Weber (Aquatic Ecology, 2022)

Editorial: Working Towards a Blue Future: Promoting Sustainability, Environmental Protection and Marine Management: Examples from the UK Government Blue Belt Programme and Current International Initiatives - Paul Whomersley; James Bell; Elizabeth Clingham; Martin A. Collins; David A. Feary; Joanna Stockill; Sam Weber; Oliver Yates; Kylie Bamford (Frontiers in Marine Science, 2022)

An Assessment of Economic Viability of the Ascension Island Tuna Longline Fishery Management: Implications for Marine Protected Area Planning and Future Fisheries Management - Angela Muench; Elena Mengo; Sam Weber; Diane Baum; Andrew James Richardson; Hannah Thomas; Paul Whomersley (Frontiers in Marine Science, 2022)
The designation of large scale marine protected areas (MPAs) has increased in recent years to address global issues such as biodiversity loss and the conservation of vulnerable marine habitats. While designing a large scale MPAs in the Exclusive Economic Zone (EEZ) of Ascension Island, the monitoring and enforcement costs were estimated for the two options under consideration: partial closure or full closure of the EEZ for the international commercial fleet. It was found that number of licenses to be sold to the international fleet to allow them access to the EEZ of Ascension Island would need to be increased to fund the monitoring and enforcement cost in case of a partial closure of the EEZ of Ascension Island. In this study, the future economic viability of the licensed big eye tuna fishery was addressed. The study explored economic drivers thought to be linked to license sales. It was shown that cost of licenses had not caused the observed decline in license sales but a shift in consumer demand toward lighter tuna species resulted in a decrease in Japanese imports for bigeye tuna ( Thunnus obesus ). This change in demand led to global changes in fishing effort and a drop in demand for licenses to fish within the Ascension Island EEZ. This study provided a valuable insight into the economic viability of the bigeye tuna fishery within the Ascension Island EEZ which informed the subsequent decision to close the bigeye tuna fishery as part of the designation of an Ascension Island highly protected large-scale MPA.

Year-Round Movements of Sooty Terns (Onychoprion fuscatus) Nesting Within One of the Atlantic’s Largest Marine Protected Areas - S. James Reynolds; Colin P. Wearn; B. John Hughes; Roger C. Dickey; Lucy J. H. Garrett; Sean Walls; Fay T. Hughes; Nicola Weber; Sam B. Weber; Eliza H. K. Leat; Kenickie Andrews; Jaime A. Ramos; et al. (Frontiers in Marine Science, 2021)
Seabirds are among the most threatened birds as a result of acute exposure to many anthropogenic threats. Their effective conservation requires a detailed understanding of how seabirds use marine habitats. Recently, one of the largest no-take marine reserves in the Atlantic was designated in tropical waters surrounding Ascension Island, on which the largest Atlantic population of sooty terns ( Onychoprion fuscatus ) breeds. Although they are the most abundant tropical seabird, they appear to have suffered marked population declines on Ascension Island as they have elsewhere. Here, we describe year-round movements and habitat use of male and female sooty terns between 2011 and 2015. On average, birds traveled 47,000 km during their 8 months of migration, during which they remained within 2,900 km of the island. They spent most of the day and night in flight, only touching down briefly on the ocean most likely to feed. Habitat suitability models successfully predicted foraging ranges of birds and their at-sea distributions varied considerably between seasons, years and sexes. Considerable variation in range overlap between birds and the new marine protected area (MPA) suggests that similar such studies of other marine taxa are urgently needed. The range of sooty terns mainly falls in the high seas outside of the new MPA, highlighting the very large areas that many oceanic seabirds forage across and the challenges their conservation present.

Spatial Variation in Pelagic Wildlife Assemblages in the Ascension Island Marine Protected Area: Implications for Monitoring and Management - Christopher D. H. Thompson; Jessica J. Meeuwig; Judith Brown; Andrew J. Richardson; Alan M. Friedlander; Peter I. Miller; Sam B. Weber (Frontiers in Marine Science, 2021)
Bathymetric features such as islands and seamounts, as well as dynamic ocean features such as fronts often harbour rich marine communities. We deployed mid-water baited remote underwater video systems on three expeditions in Ascension Island’s Exclusive Economic Zone (EEZ), surveying the waters associated with six different bathymetric and dynamic ocean features: Ascension Island, two shallow seamounts (summits ≤ 101 m), one deeper seamount (summit > 250 m), apparent fronts, and haphazardly sampled open ocean areas. At Ascension Island, the pelagic assemblage consisted of a moderate proportion of predators and a diverse range of other taxa, including turtles, dolphins, and large non-piscivores. At the two shallow seamounts, sharks, tunas, billfish, and other large pelagic predators formed the vast majority of the assemblage, contributing > 99.9% of biomass and > 86% of abundance. At the deeper seamount, the pelagic community was comparatively depauperate, however the functional composition of its assemblage indicated some similarities to the shallow seamounts. Apparent fronts did not significantly differ from random offshore sites for metrics such as total abundance and taxonomic richness. However, they harboured assemblages with more abundant sharks, tunas, and large piscivores than random ocean open locations and these differences may be driven by certain front-associated species. Our results illustrate that pelagic assemblages vary markedly among different physical and oceanographic features and that seamounts appear particularly important for pelagic predators. The diversity and abundance of the assemblage, as well as the threatened status of many of the species observed, serve to highlight the conservation value of the Ascension Island EEZ. Our results also provide important baseline information of pelagic wildlife assemblages against which the performance of the recently implemented Ascension Island Marine Protected Area can be evaluated.

Bridging From Monitoring to Solutions-Based Thinking: Lessons From CalCOFI for Understanding and Adapting to Marine Climate Change Impacts - Natalya D. Gallo; Elizabeth Drenkard; Andrew R. Thompson; Edward D. Weber; Deb Wilson-Vandenberg; Sam McClatchie; J. Anthony Koslow; Brice X. Semmens (Frontiers in Marine Science, 2019)

Long‐term dietary shift and population decline of a pelagic seabird—A health check on the tropical Atlantic? - S. James Reynolds; B. John Hughes; Colin P. Wearn; Roger C. Dickey; Judith Brown; Nicola L. Weber; Sam B. Weber; Vitor H. Paiva; Jaime A. Ramos (Global Change Biology, 2019)
In the face of accelerating ecological change to the world's oceans, seabirds are some of the best bio‐indicators of marine ecosystem function. However, unravelling ecological changes that pre‐date modern monitoring programmes remains challenging. Using stable isotope analysis of feathers and regurgitants collected from sooty terns ( Onychoprion fuscatus ) nesting at a major Atlantic colony, we reconstructed a long‐term dietary time series from 1890 to the present day and show that a significant dietary shift occurred during the second half of the twentieth century coinciding with an apparent population collapse of approximately 84%. After correcting for the “Suess Effect,” δ 13 C in feathers declined by ~1.5‰ and δ 15 N by ~2‰ between the 1890s and the present day, indicating that birds changed their diets markedly over the period of population decline. Isotopic niches were equally wide before and after the population collapse but isotopic mixing models suggest that birds have grown ever more reliant on nutrient‐poor squid and invertebrates as teleost fish have declined in availability. Given that sooty terns rely heavily on associations with sub‐surface predators such as tuna to catch fish prey, the rapid expansion of industrialized fisheries for these species over the same period seems a plausible mechanism. Our results suggest that changes to marine ecosystems over the past 60 years have had a dramatic impact on the ecology of the most abundant seabird of tropical oceans, and highlight the potentially pervasive consequences of large predatory fish depletion on marine ecosystem function.

Foraging distribution of a tropical seabird supports Ashmole’s hypothesis of population regulation - Steffen Oppel; Annalea Beard; Derren Fox; Elizabeth Mackley; Eliza Leat; Leeann Henry; Elizabeth Clingham; Nathan Fowler; Jolene Sim; Julia Sommerfeld; Nicola Weber; Sam Weber; et al. (Behavioral Ecology and Sociobiology, 2015)

Long Time Series in US Fisheries Oceanography - Sam McClatchie; Janet Duffy-Anderson; John Field; Ralf Goericke; Dave Griffith; David Hanisko; Jonathan Hare; Joanne Lyczkowski-Shultz; William Peterson; William Watson; Edward Weber; Glenn Zapfe (Oceanography, 2014)

Recovery of the South Atlantic’s largest green turtle nesting population - Sam B. Weber; Nicola Weber; Jacqui Ellick; Andrew Avery; Robert Frauenstein; Brendan J. Godley; Jolene Sim; Natasha Williams; Annette C. Broderick (Biodiversity and Conservation, 2014)

Comparison of indigenous and exogenous microbial populations during slurry phase biodegradation of long-term hydrocarbon-contaminated soil - Arturo Aburto-Medina; Eric M. Adetutu; Sam Aleer; John Weber; Sayali S. Patil; Petra J. Sheppard; Andrew S. Ball; Albert L. Juhasz (Biodegradation, 2012)